DEVELOPMENT OF BUSINESS COMMUNICATIONS AS AN ELEMENT OF CORPORATE CULTURE MANAGEMENT - PYSAREVSKA, Hanna; SHUBA, Tetiana; VAVILOV, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the article is to analyze and summarize the modern practice of using business communications in the process of corporate culture management on the principles of digitalization. The key aspects of the impact of corporate culture on the efficiency of the organization, its cohesion, adaptability to changes and competitiveness in the modern market environment are studied. The article states that corporate culture is not only a tool for regulating employee behavior, but also a source of motivation, loyalty and innovation. It forms a sense of social security among employees, creates a common system of values and ensures the achievement of the company's strategic goals by strengthening trust, integrating teams and supporting an innovative environment. Particular attention is paid to the transformation of business communications under the influence of digitalization. The authors analyze digital tools used to improve corporate culture, including project management platforms, communication tools, digital services for training staff and monitoring team sentiment. Their impact on creating a transparent work environment, accelerating decision-making and forming an innovative atmosphere is determined.Modern models of corporate culture management are studied, including adaptation to change, employee socialization through training, an emphasis on leadership and the use of digital technologies. The authors conclude that a flexible combination of these approaches is the most effective for maintaining a company's competitiveness.The article also provides practical recommendations for the implementation of the latest technologies in business communications, such as artificial intelligence, big data and virtual reality, which contribute to creating conditions for sustainable development and ensure integration between organizational units.The study emphasizes the need for systematic improvement of business communications as a means of increasing productivity, strengthening corporate spirit and supporting the emotional well-being of employees.The results of the study have both theoretical and practical significance, as they offer tools and strategies that help organizations adapt to change and lay the foundation for long-term success. The directions of further research are the justification of the tools for the practical implementation of business communications based on digitalization in the management of the corporate culture of domestic enterprises
Keywords: business communications; corporate culture; digital tools; digitalization